POŁOŻENIE PRAWNE FILIAE FAMILIAS I JEJ UDZIAŁ W OBROCIE PRAWNO-GOSPODARCZYM PAŃSTWA RZYMSKIEGO W OKRESIE PÓŹNEJ REPUBLIKI I PRYNCYPATU (ZARYS PROBLEMATYKI) - Ejankowska, Elżbieta (Zeszyty Prawnicze, 2017)
Legal Situation of the filiae familias and its Significance in Legal and Commercial Transactions in the Roman State during the Period of the Late Republic and Principate (an Outline of the Issues) Summary The legal and economic situation of the filiae fanilias is presented against the background of political and social-economic changes in two different political systems of the state, the common characteristics of which were that they constituted consecutive stages of advanced Roman civilization. The period faced an increase in the significance of women, although - regardless their status familiae - they were formally excluded from the public life and deprived of certain rights in the domain o f private law. Nevertheless, social and economic changes, resulting from the territorial expansion of Rome, made it possible for Roman women to expand their activities beyond the scope of the matters related to every day existence, family and religion, which traditionally for centuries had been considered as a women’s domain. As far as the social aspect o f Roman wom en’s activities is concerned, their status fam iliae seemed to be o f no major importance. As regards commercial aspects, the situation was different. In this respect, the sui iuris women unquestionably enjoyed richer possibilities. Nevertheless, as the analysis o f legal and literary sources show, women subject to the authority o f a family superior - although having no possibility to be carriers o f property rights or to enjoy private autonomy - could in fact influence their economic situation, similarly to slaves. It was possible mainly due to peculium that stemmed from the common law, which played a significant role in the social - economic life o f the Roman state. It was of a particular significance in the case of women who were subject to familial authority, but were married. This resulted from the fact that managing a trust property and using the earned income made it possible for women to enjoy certain economic freedom, and, as a consequence, become independent of her husband or his family superior. Undoubtedly, the expansion and diversification of the activities o ffiliae familias were influenced by the actiones adiecticiae qualitatis, which uniformly regulated the responsibilities of the holders of authority for the liabilities of the alieni iuris persons and slaves. Moreover, parties to contracts with the family could file such claims, as the aforesaid sources have proved, which meant that the praetor’s law offered a guarantee that they could pursue such claims before courts. Consequently, the participation of women subject to familial authority in commercial transactions had to become wider. Although still a dominant role was played by the family’s slaves and sons, women were present in the legal and economic field during periods of the Late Republic and the Principate.